ANALISIS KOMPREHENSIF PERLINDUNGAN HUKUM MEREK DAGANG DALAM BISNIS DI INDONESIA: Comprehensive Analysis of Legal Protection for Trademarks In Business In Indonesia - Rahman, Erval Ade (Fakultas Hukum Universitas Komputer Indonesia, 2025)
Legal protection of trademarks in Indonesia, regulated by Law No. 20 of 2016 on Trademarks and Geographical Indications, plays a crucial role in shaping the competitive conditions in the market. This article analyzes the impact of trademark protection on market competition and industry dynamics in Indonesia. The study identifies that effective protection can reduce unfair competition practices, such as counterfeiting and brand imitation, as well as encourage investment and innovation among businesses. Trademark protection also contributes to market transparency and enhances consumer trust. However, significant challenges are faced by small and medium-sized enterprises (SMEs), which often struggle to access trademark protection due to costs and administrative complexity. The article also proposes the need for reforms in the registration and enforcement systems to create a more inclusive and fair business environment. By analyzing various recent studies and references, this research provides insights into how trademark protection can affect competitive conditions and business strategies in Indonesia.